PENGARUH PENAMBAHAN FILLER BLOTONG TERHADAP POTENSI CAKING PUPUK MAJEMUK GRANUL - K Kasmadi; Budi Nugroho; Atang Sutandi; Syaiful Anwar (Jurnal Tanah dan Sumberdaya Lahan, 2020)
The physical quality of NPK fertilizer is very important, good physical quality, as indicated by the low potential of caking and absorption-penetration of water so that NPK fertilizer can be stored for a longer time and easier in handling. In this study, the granulation test used NPK 15-15-15 + 5S formula with the percentage filter pressmud 0%, 60%, 70%, 80%. 90% and 100% in two types of K sources: MOP (KCl) and SOP (K2SO4). Granulation was carried out using the wet granulation method using pan granulator, 2 kg batch-1 capacity, rotation speed 23 rpm and 50o pan slope. The purpose of this study was to determine the effect of filter pressmud addition on the tendency of caking NPK 15-15-15 + 5S products during storage. The results showed that the addition of pressmud filler in the production of NPK fertilizer was obtained: the addition of filter pressmud as a filler in the production of 15-15-15 + 5S NPK fertilizers can reduce the potential of caking by 1.77% -44.31% depending on the formulation of raw materials used.